The Impact of Innovation, Economic Growth, and Renewable Energy on CO2 Emissions in Developing Countries - Amankeldi, Nazigul; Parmanova, Rimma; Azretbergenova, Gulmira; Abdildinova, Nailya (International Journal of Energy Economics and Policy, 2025)
This study examines the impact of economic growth, innovation, foreign trade, and renewable energy consumption on environmental sustainability in ten developing countries over the period 2000–2023. Based on panel data analysis, the research identifies strong cross-sectional dependence and structural heterogeneity among the countries. The results of the Westerlund and Edgerton (2007) cointegration test indicate the existence of a long-term relationship among the variables. According to the AMG estimator results, economic growth and renewable energy consumption exert a mitigating effect on carbon emissions. In contrast, the innovation variable increases emissions in the short run, suggesting that innovation activities have not yet fully shifted toward environmentally friendly technologies. The effect of foreign trade on carbon emissions, however, is found to be statistically insignificant. Overall, the findings suggest that achieving environmental sustainability in developing countries requires harmonizing economic growth with environmental policies. The study emphasizes the need to promote green innovation, increase investments in renewable energy, and support environmentally friendly production processes. In this context, it is recommended that environmental, energy, and innovation policies be implemented within an integrated development strategy.